P144 Impact of major medication discontinuation during the first wave of COVID-19 pandemic on the risk of early relapse in patients with inflammatory bowel disease: a French observational retrospective study. (30th January 2023) - Meunier, C; Monte, C; Hadjisavvas, H; Rozieres, A; Roblin, X; Venturin, C; Gay, C; Flourie, B; Boschetti, G; Danion, P; Mathieu, N; Charlois, A L; et al.
Abstract: Background: The prevalence of nonadherence to major treatments and the subsequent adverse outcomes in IBD patients during the first wave of COVID-19 pandemic remain scarce. Aim: to investigate the risk of early disease relapse in a cohort of IBD patients under immunosuppressants and/or biologics who decided themselves to discontinue their IBD-related major treatments without previous medical advice during the first wave of COVID-19 pandemic. Methods: All consecutive patients with inactive IBD under immunosuppressants and/or biologics who acknowledged having withdrawn their major therapy for IBD without previous medical advice during the first wave of COVID-19 (from March 2020 to December 2020) were enrolled. The primary endpoint was the survival rate without disease relapse. Kaplan-Meier curves were plotted for time from inclusion to IBD relapse and a logistic regression model with uni- and multivariate analyses was performed to identify predictors of relapse after drug discontinuation. Results: During the study period, among the 862 IBD patients followed as outpatients either treated with infliximab or vedolizumab (outpatient clinics n= 368) or treated with oral azathioprine, adalimumab, golimumab or ustekinumab alone or in combination (n= 494), 54 patients (6.2 %) (42 CD, 12 UC, 28 F, median age 36 years) who had discontinued themselves their IBD-related major therapy without previous medical advice were included. The median duration of drug withdrawal was 7.0 weeks (range 2-24) and the median time to relapse was 9.0 weeks (range 4-20). The most treatments withdrawn were adalimumab (n=19), ustekinumab (n=19), azathioprine (n= 12), golimumab (n=1) and a lesser degree infliximab (n=7) eand vedolizumab (n=6). During the median follow-up period of 24 weeks (range 5-42), 22 out of 54 patients (40.7 %) who discontinued their IBD treatment experienced a relapse in whom 6 requiring administration of oral steroids, 4 hospitalization and 2 IBD-related surgery. By univariate analysis, past IBD related surgery was identified as the only predictor of disease relapse after drug withdrawal (OR=3.3 CI 95 % [1.08-10.38]. Conclusion: In IBD patients, major treatment discontinuation by the patients themselves without medical advices during the first wave of pandemic Covid-19 including the lockdown was associated with a substantial risk of disease relapse occurring in around 4 out of 10 patients and subsequent further risk of need for steroids, hospitalization and surgery. Strategies targeting the adherence to therapy and patient's informations about the real risks leading to drug discontinuation are of paramount interest, especially during health crisis to minimize such issues.